2014
DOI: 10.1121/1.4835735
|View full text |Cite
|
Sign up to set email alerts
|

Training improves cochlear implant rate discrimination on a psychophysical task

Abstract: The purpose of this study was to determine the extent to which cochlear implant (CI) rate discrimination can be improved through training. Six adult CI users took part in a study that included 32 h of training and assessment on rate discrimination measures. Rate difference limens (DLs) were measured from 110 to 3520 Hz in octave steps using 500 ms biphasic pulse trains; the target and standard stimuli were loudness-balanced with the target always at an adaptively lower rate. DLs were measured at four electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…It is unclear which factors determine the ability to exploit ITDs at high modulation frequencies, although it appears that some listening experience is necessary, although not sufficient, to generate high performance or low thresholds. Note that Goldsworthy and Shannon (2014) found that 32 hr of training improved rate difference limens in CI listeners by a factor of two, suggesting that training in the task might be an important factor. One limitation for correct lateralization with increasing modulation rate is that the limiting value of half the period of the modulation will start to encroach on the range of potential ITD thresholds.…”
Section: Discussionmentioning
confidence: 94%
“…It is unclear which factors determine the ability to exploit ITDs at high modulation frequencies, although it appears that some listening experience is necessary, although not sufficient, to generate high performance or low thresholds. Note that Goldsworthy and Shannon (2014) found that 32 hr of training improved rate difference limens in CI listeners by a factor of two, suggesting that training in the task might be an important factor. One limitation for correct lateralization with increasing modulation rate is that the limiting value of half the period of the modulation will start to encroach on the range of potential ITD thresholds.…”
Section: Discussionmentioning
confidence: 94%
“…The advent of relatively inexpensive personal computers has made it possible to automate many common training routines, making computerized training a practical, low-cost approach for improving patient auditory perception (Henshaw & Ferguson, 2013;Pizarek, Shafiro, & McCarthy, 2013). A number of training programs, targeting different aspects of auditory perception and cognitive processing, have been tested with CI patients (Dawson & Clark, 1997;Fu & Galvin, 2007;Gfeller, Witt, Kim, Adamek, & Coffman, 1999;Goldsworthy & Shannon, 2014;Ingvalson, Lee, Fiebig, & Wong, 2013;Miller, Watson, Kistler, Wightman, & Preminger, 2008;Oba, Fu, & Galvin, 2011;Stacey et al, 2010;Wu, Yang, Lin, & Fu, 2007;Zhang, Dorman, Fu, & Spahr, 2012). Training studies with CI patients differ considerably in terms of study design, training regimens, materials, and outcome measures.…”
Section: Computerized Training In Cochlear Implant Rehabilitationmentioning
confidence: 99%
“…This suggests that at high rates, pitch was not a reliable explanation for the perceptual differences between higher rates of stimulation. Nevertheless, Goldsworthy and Shannon (2014) were able to train listeners to pitch rank higher rates of stimulation (up to 3520 Hz) correctly. Further study is needed to understand the perceptual changes produced by a change in carrier rate.…”
Section: Experiments 2b—sound Quality Scaling Of Analog and Amp Stimulmentioning
confidence: 91%